UJI EFEK ANTIINFLAMASI EKSTRAK ETANOL DAUN BINAHONG (Anrederacordifolia) SECARA ORAL - Yuziani Yuziani (Pascasarjana Universitas Negeri Medan, 2015)
Abstrak. Binahong (Anrederacordifolia) is a type of creeping plants basellaceae family members are empirically used by the public to assist in the healing of various diseases, among them for treating wounds or speed the drying process. The most widely used in the treatment is the leaves, although there has been no clinical data on efficacy. Binahong contains saponins, triterpenoids, flavonoids and essential oils . Flavonoids are compounds that have a variety of different bioactivit, including analgesics and anti-inflammatory. The purpose of this study is to see anti-inflammatory effects of ethanol extract of leaves binahong orally to rats. The study was conducted experimentally to test the analgesic activity of orally . In this study, the research subjects were Wistar rats and plant extract made by maceration binahong using 96 % ethanol, then ethanol extract of leaves binahong divided into three doses are dose of 100 mg / kg bw, 200 mg / kg bw, 400 mg / kg bb. Physics run private pain inducers used tool in which the rat plantar test infra-red transmitter is placed at the foot of rats and mice ever seen interesting and lick her feet. Diclofenac sodium is used as a positive comparison . The data obtained were statistically tested using ANOVA (n = 6 , P > 0.05). Result data shows that (1) there were a significantly antiinflammatory effect of oral test showed that inflammation persetase EEDB at a dose of 100mg / kg bw, 200 mg / kg bw and 400 mg / kg bw different between SND 2.25 mg / kg bw. (2) The percentage inflammation SND 2,25 mg / kg bw , followed by EEDB 400 mg / kg bw , 200 mg / kg bw and 100 mg / kg bw . (3) Result data which is indicated by Ducan test that SND 2.25% mg / kg bw show most excellent anti-inflammatory effects in follow EEDB dose of 400 mg / kg bw . This shows that an increase in the effect is directly proportional to the dose. Research shows that the ethanol extract of the leaves have anti-inflammatory activity binahong statistically similar with diclofenac sodium . Preparations Binahong leaf ethanol extract tested showed good results as anti-inflammatory at a dose of 400 mg / kg bw compared with a dose of 100 mg / kg bw and 200 mg / kg bwKeywords: Test Antiinflamasi , Ethanol Extracts , Leaf Binahong , Oral